Spider-girl. Vol. 3 Avenging allies - DeFalco, Tom.; Olliffe, Pat.; Williamson, Al 1931-.; Buscema, Sal. (New York Marvel Comics, 2005)
The adventures of Spider-Man's daughter continue as Mayday Parker faces defeat and disgrace at the hands of Darkdevil, the Avengers, and Kaine! Plus: Beset by problems in her civilian guise, Spider-Girl teams up with Speedball to take on Mr. Abnormal!
"Contains material originally published in magazine form as Spider-Girl #12-16 and '99 annual"--P. [2 of cover].
UCWS-2790g donated by Tristan Manalastas - January 2016
Keywords: Spider-Girl (Series).; Women heroes -- Comic books, strips, etc. -- Fiction; Graphic novels; Comic books, strips, etc; CHR 2005.